Goal orientation, anxiety and performance in sports : a population based study - Grímur Gunnarsson 1990- (2021)
The world of sports has embraced the fact that psychological factors can deeply impact athletic performance. The current study was conducted to assess the effect of sport anxiety and goal orientation on an endurance test performance of adolescent soccer players. The participants were 56% of all registered 16 year old soccer players in Iceland in 2020-2021 (N = 826). Thereof were 625 boys and 201 girls. The Sport Anxiety Scale-2 and The Task and Ego Orientation in Sport Questionnaire were used and The Yo-Yo Intermittent Endurance Test Level 2 for endurance testing. Results on gender differences supported existing research that girls experience more sport related anxiety symptoms and are higher than boys on task orientation. Correlation analysis showed a significant negative relationship between anxiety and endurance test performance for both genders with anxiety having more severe impact on the girls performance. Finally, a one-way ANCOVA with Bonferroni post-hoc assessing the effect of goal orientation profile on Yo-Yo test performance demonstrated a significant difference between the Low Task/Low Ego group and the High Task/High Ego and High Task/Low Ego groups with total anxiety score as covariate for boys. No significant difference was found between the girls goal orientation profiles. The findings suggest that in sports, where the margin for error is so small, performance anxiety can be a deciding factor, and should therefore be a prime target for everyone involved. Finally, the results support the notion that task orientation development in sports should be a primary focus from young age. Keywords: sport anxiety, goal orientation, performance, adolescence, sport psychology, gender, endurance, soccer.